2005
DOI: 10.1007/bf03165830
|View full text |Cite
|
Sign up to set email alerts
|

International perspectives on early childhood curricula

Abstract: The early years of childhood are receiving increased public policy attention in many countries around the world. Debates on providing quality services and ensuring a good foundation for lifelong learning are generating a new interest in curriculum issues. What understandings do we have of young children? How do they access and construct knowledge about the world around them? What can adults do to effectively enhance children's learning opportunities? According to prevailing values, traditions and priorities, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
18

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 8 publications
2
35
0
18
Order By: Relevance
“…Consistent with the findings from international research (Oberhuemer, 2005;Alvestad & Duncan, 2006;Nuttall & Edwards, 2007;Sofou & Tsafos, 2010) was the way the EYLF provided a language and a vehicle for articulating the work of early childhood educators. In addition, the EYLF seems to have given authority to the education discourse of early childhood because of its positioning as 'independent', 'national' and supported by research and government.…”
Section: Taking Up Official Curriculum Discoursessupporting
confidence: 56%
See 1 more Smart Citation
“…Consistent with the findings from international research (Oberhuemer, 2005;Alvestad & Duncan, 2006;Nuttall & Edwards, 2007;Sofou & Tsafos, 2010) was the way the EYLF provided a language and a vehicle for articulating the work of early childhood educators. In addition, the EYLF seems to have given authority to the education discourse of early childhood because of its positioning as 'independent', 'national' and supported by research and government.…”
Section: Taking Up Official Curriculum Discoursessupporting
confidence: 56%
“…This study found that teachers 'made sense of a national curriculum text within complex and contradictory contexts and discourses' (Sofou & Tsafos, 2010, p. 419). Enhanced professionalism, where practitioners have exercised autonomy in making their own interpretations and curriculum decisions within a unifying framework, allows practitioners to take ownership of the curriculum (Oberhuemer, 2005;Alvestad & Duncan, 2006). Oberhuemer (2005) argues that early childhood educators need the opportunity to clarify their own thinking on professionalism, and to reposition themselves in ways that can accommodate the new expectations that come with new curriculum documents.…”
Section: The Impact Of Curriculum Documents On Professional Identitiesmentioning
confidence: 99%
“…She claims: "If we all believe that we are so unique in each culture, we end up in a relativity where there are no human rights!" Curricula for early childhood education and care vary not only in scope, objectives and evaluation (Oberheumer, 2005), but also in methods or perspectives on children and their play and learning (Alvestad & Pramling Samuelsson, 1999;Karlsson Lohmander & Pramling Samuelsson, 2002.…”
Section: A Global Perspective Of Curricula For Early Childhood Educatmentioning
confidence: 99%
“…Haridusteaduste instituut, Tallinna Ülikool, Narva mnt 25, 10120 Tallinn; neudorf@tlu.ee riiklikke õppekavu (Bennett, 2005;Oberhuemer, 2005aOberhuemer, , 2005bUrban & Dalli, 2008;Urban, Vandenbroeck, van Laere, Lazzari, & Peeters, 2012), pöö-rata suuremat tähelepanu laste koolivalmiduse tagamisele ning õpitegevustele (Belfield & Garcia, 2014;Einarsdottir, 2006;Platz & Arellano, 2011;Puccioni, 2015), standardiseeritult hinnata laste õpi-ja arengutulemusi (Gunnarsdottir, 2014) ning rangemalt reguleerida lasteaiaõpetajate professionaalsuse nõudeid (Osgood, 2009;Urban, 2008). Need tendentsid ilmnevad hoolimata sellest, et Euroopa Komisjoni, UNESCO ja teiste rahvusvaheliste organisatsioonide konsensusliku arusaama järgi on alusharidus laiapõhjaline ja holistlik ning toetab laste õpetamist, kasvatamist ja arendamist tasakaalustatult .…”
Section: Sissejuhatusunclassified